2019
DOI: 10.1177/0265532219849522
|View full text |Cite
|
Sign up to set email alerts
|

The effect of training and rater differences on oral proficiency assessment

Abstract: As a result of the fact that judgments of non-native speech are closely tied to social biases, oral proficiency ratings are susceptible to error because of rater background and social attitudes. In the present study we seek first to estimate the variance attributable to rater background and attitudinal variables on novice raters’ assessments of L2 spoken English. Second, we examine the effects of minimal training in reducing the potency of those trait-irrelevant rater factors. Accordingly, we examined the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 52 publications
2
38
0
Order By: Relevance
“…Current research is equivocal on the effect of listeners' linguistic knowledge and educational accomplishment on the assessment of L2 performance. The findings of the study conducted by Kang et al [3] did not reveal any significant relation between the degree of educational accomplishment and linguistic knowledge on listeners' holistic ratings of L2 proficiency. Also, listeners varying in degrees of educational accomplishment did not differ in rating severity; nevertheless, those listeners who were extremely severe or lenient in their assessments, regardless of their educational background, became more moderate after they received training and became familiar with assessment criteria.…”
Section: Listener Educational Background and Linguistic Knowledgementioning
confidence: 64%
See 4 more Smart Citations
“…Current research is equivocal on the effect of listeners' linguistic knowledge and educational accomplishment on the assessment of L2 performance. The findings of the study conducted by Kang et al [3] did not reveal any significant relation between the degree of educational accomplishment and linguistic knowledge on listeners' holistic ratings of L2 proficiency. Also, listeners varying in degrees of educational accomplishment did not differ in rating severity; nevertheless, those listeners who were extremely severe or lenient in their assessments, regardless of their educational background, became more moderate after they received training and became familiar with assessment criteria.…”
Section: Listener Educational Background and Linguistic Knowledgementioning
confidence: 64%
“…Hsieh reported that English as a second language (ESL) teachers were more lenient in their ratings of ITAs' oral proficiency, comprehensibility, and accentedness than American undergraduates with no teaching experience. However, in a more recent study, Kang et al [3] did not find a statistically significant relationship between listeners' amount of teaching experience and their holistic ratings as well as their rating severity of L2 proficiency. Thus, although listeners who possess language teaching experience are assumed to be more lenient than their counterparts with no experience in teaching, this leniency is not consistent across the board.…”
Section: Effects Of Prior Language Teaching and Tutoring Experiencementioning
confidence: 84%
See 3 more Smart Citations